Assessment of the laser floating zone processing of thermoelectric CuFe1–xNixO2 delafossites and their magnetic characterisation - Ferreira, N. M. (2024)
This work assesses the feasibility of processing CuFe1-xNixO2 (x = 0, 0.02) using the Laser Floating Zone (LFZ) technique to grow fibres with different pulling rates, to tune their thermoelectric performance. Structural analysis showed CuFeO2 as the major phase. Formation of secondary phases is promoted by Ni addition, diminishing with decreasing pulling rate. Grain alignment and crystallite size of the fibres increase with the puling rate and doping. Electrical conductivity is enhanced by decreasing the pulling rate, while Ni-doping decreases the conductivity, and Seebeck coefficient demonstrates quite complex behaviour. Thermal conductivity decreases with temperature and with the pulling rate and Ni-doping. A maximum ZT value of 0.17 was achieved for 10 mm h-1 sample at 1000 K for pure, and 700 K for Ni-doped samples. These ZT values are higher than found in the literature, demonstrating the feasibility of the LFZ method for processing thermoelectric delafossites, indicating a proper optimisation process